Three patients resembling Teebi–Shaltout syndrome. Issue 10 (5th August 2013) - Aldemir, Ozgur; Ozen, Samim; Erdem, Sevcan; Kiraz, Aslihan; Akarsu, Nurten; Alanay, Yasemin
ABSTRACT Teebi–Shaltout syndrome (TSS) was first reported by Teebi and Shaltout in 1989. This entity is proposed to be inherited in autosomal recessive manner. The clinical features include characteristic facial features, ectodermal dysplasia, camptodactyly, and caudal appendage. Only one additional paper reporting four additional cases has been published since the first description. Clinical features common to all previously affected individuals diagnosed with TSS are craniofacial, orodental‐ectodermal, and skeletal. This report summarizes and discusses the findings of three additional patients from two unrelated families with findings similar to TSS. These findings may be present in a genetically and phenotypically heterogeneous group of disorders similar to TSS. Presence of consanguinity and similarly affected siblings of both genders suggests autosomal recessive inheritance. © 2013 Wiley Periodicals, Inc.